The global effects of global risk and uncertainty - Dario Bonciani; Martino Ricci (European Central Bank (ECB), 2018)
In this paper, we analyse the effects of a shock to global fnancial uncertainty and risk aversion on real economic activity. To this end, we extract a global factor, which explains approximately 40% of the variance of about 1000 risky asset returns from around the world. We then study how shocks to the factor affect economic activity in 36 advanced and emerging small open economies by estimating local projections in a panel regression framework. We find the output responses to be quite heterogeneous across countries but, in general, negative and persistent. Furthermore, the effects of shocks to the global factor are stronger in countries with a higher degree of trade and/or financial openness, as well as in countries with higher levels of external debt, less developed financial sectors, and higher risk rating.
Keywords: C30; F41; E32; F65; 330; Global Financial Cycle; Local Projection; Macroeconomic Transmission; Panel Data